The PHANGS-HST-Hα survey: warm ionized gas physics at high angular resolution in nearby galaxies with the Hubble Space Telescope - Chandar, Rupali; Barnes, Ashley T.; Thilker, David A.; Caputo, Miranda; Floyd, Matthew R.; Leroy, Adam K.; Úbeda, Leonardo; Lee, Janice C.; Boquien, Médéric; Maschmann, Daniel; Belfiore, Francesco; Kreckel, Kathryn; et al. (The astronomical journal, 2025)
The PHANGS project is assembling a comprehensive, multiwavelength data set of nearby (∼5-20 Mpc), massive star-forming galaxies to enable multiphase, multiscale investigations into the processes that drive star formation and galaxy evolution. To date, large survey programs have provided molecular gas (CO) cubes with the Atacama Large Millimeter/submillimeter Array, optical integral field unit (IFU) spectroscopy with the Very Large Telescope/Multi-Unit Spectroscopic Explorer (MUSE), high-resolution near-ultraviolet-optical imaging in five broadband filters with Hubble Space Telescope (HST), and infrared imaging in NIRCAM+MIRI filters with JWST. Here we present PHANGS-HST-Hα, which has obtained high-resolution (∼2-10 pc), narrowband imaging in the F658N or F657N filters with the HST/WFC3 camera of the warm ionized gas in the first 19 nearby galaxies observed in common by all four of the PHANGS large programs. We summarize our data reduction process, with a detailed discussion of the production of flux-calibrated, Milky Way extinction-corrected, continuum-subtracted Hα maps. PHANGS-MUSE IFU spectroscopy data are used to background-subtract the HST-Hα maps and to determine the [N ii] correction factors for each galaxy. We describe our public data products (the data released as part of this work include the reduced drizzled narrowband images and the flux-calibrated, continuum-subtracted Hα maps for each galaxy; these images are available for download via MAST at https://archive.stsci.edu/hlsp/phangs.html, as well as at the Canadian Astronomy Data Centre as part of the PHANGS archive at https://www.canfar.net/storage/vault/list/phangs/RELEASES) and highlight a few key science cases enabled by the
Online veröffentlicht am 18. Februar 2025
Gesehen am 08.12.2025